Low cost image-based modeling techniques for archaeological heritage digitalization: more than just a good tool for 3d visualization? - Mariateresa Galizia; Cettina Santagati (Virtual Archaeology Review)
This study shows the first results of a research aimed at catching the potentiality of a series of low cost, free and open source tools (such as ARC3D, 123D Catch, Hypr3D). These tools are founded on the SfM (Structure from Motion) techniques and they are able to realize automatically image-based models starting from simple sequences of pictures data sets. Initially born as simple touristic 3D visualization (e.g. Photosynth) of archaeological and/or architectural sites or cultural assets (e.g. statues, fountains and so on), nowadays allow to reconstruct impressive photorealistic 3D models in short time and at very low costs. Therefore we have chosen different case studies with various levels of complexity (from the statues to the architectures) in order to start a first testing on the modeling potentiality of these tools.